Gum Arabic more than emulsiﬁer and food additive: a new experimental validation of anti-proliferative against colorectal colon cancer cell lines - Elnour, Ahmed Adam Hassan M.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Daddiouaissa, Djabir; Musa, Khalid Hamid; Nour, Abdurahman Hamid (World Association for Sustainable Development (WASD), 2020)
The aim of this paper is to discover the cytotoxicity activity of Acacia seyal gum and Prebio-Tcommercial (PTC) samples on human colon cancer (HCT-116) cell lines; in addition, its polyphenolic properties are investigated. Approach: The methodology used in this paper involves fractionating methanol crude extracts of both Acacia seyal gum and Prebio-T-commercial, respectively. The cytotoxicity activity on human colon cancer cell lines for each fraction was studied using sulforhodamine B assay (SRB assay). Both samples, Acacia seyal gum and Prebio-T-commercial (PTC), were analysed precisely using high performance liquid chromatography (HPLC) technique. Findings: Based on the analysis, more cytotoxicity activity was identified in the sample obtained from Acacia seyal gum (IC50=13.36µg/mL) compared to PTC (IC50=17.18µg/mL). Regarding the flavonoids content (FC), quercetin was the only flavonoids detected in the samples, found to be approximate of 4,640µg/100g for Acacia seyal gum, almost double the value of 2,560µg/100g for PTC. Implications: The implications of this study are the evidence of flavonoids content and anti-cancer activity for both Acacia seyal gum and PTC used in folk medicine, as well as anticipation of cancer cell growth. It is expected that the proposed methods will give a noble contribution to the possible use of their bioactive compounds as natural anti-cancer agents.